(untitled) (Asian Journal of Pharmaceutics (AJP), 2020)
Introduction: Enhancement of the dissolution rate and solubility of drugs by cocrystals (Cs) may be negatively affected by the manufacturing variables and storage conditions; therefore, the physical and chemical stability of the tablets should be assessed to ensure the maintenance of the Cs’ properties. Objective: The objective of the study was to formulate atorvastatin calcium-cocrystals (ATC-Cs) into tablets and investigate the effect of storage conditions on drug and quality of the developed tablets. Materials and Methods: Five tablet formulations (F1-F5) were developed by direct compression using ATC-Cs prepared by solvent drop grinding and solvent evaporation method using 1:3 drug-coformer molar ratio, using glucosamine and nicotinamide as coformers. The physicochemical properties of the ATC-Cs, their physical mixtures, and the raw ATC, before and after storage were studied by Fourier-transform infrared, differential scanning calorimetry, powder X-ray diffraction, gas chromatography-mass spectrometer, scanning electron microscopy, and dissolution rate. Results: ATC proved to be stable in the Cs and the formulated tablets at 25°C and 40°C ± 2°C/75 RH and the results, never the less after 6-months at 40°C, partial dissociation of the prepared Cs occurred due to the weak intermolecular hydrogen bonding between the drug and the coformers. The tablets exhibited an enhanced dissolution rate, similar to the innovator Lipitor® and showed satisfactory results complying with the pharmacopeial specifications. Conclusion: The developed ATC-Cs were successfully incorporated into tablets. The prepared tablets showed good quality attributes upon storage. Among all the tablet formulations, F4 was the best in terms of the pre-compression and post-compression parameters.